My little pony: legends of magic (2017), annual 2018 ebook Legends of magic annual 2018. - Whitley, Jeremy (My Little Pony: Legends of Magic (2017)., 2018)
My Little Pony: Legends of Magic wraps up in oversized fashion with this annual! The Pillars face a new danger that will test their skills as a team and take them one step closer to their fateful final encounter in ancient Equestria! Author: Jeremy Whitley. Illustrator: Brenda Hickey. © 2018 Hasbro. All Rights Reserved.